155k views
7 votes
Please awnser as quicck as possible correct

Please awnser as quicck as possible correct-example-1
User Gabe Levi
by
4.9k points

1 Answer

7 votes

Answer:

y = 2x + 2

Explanation:

Firstly find the gradient of the line using the formula;


m = (y_(2) - y_(1))/(x_(2) - x_(1))


m = (8 - 2)/(3 - 0)


m = 2

Now substitute into the formula to find the equation of a straight line;


y - y_(1) = m(x - x_(1))


y - 2 = 2(x - 0)


y = 2x + 2

User YOBA
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.